STUDENTS’ ABILITY IN USING CONDITIONAL SENTENCES - Syafrizal Azzali; Jumino Suhadi; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2023)
This research was aimed at describing the students’ ability using conditional sentences and to investigate the dominant type of conditional sentences mastered by the eleventh-grade students using conditional sentences (type I, II, and III) at SMAS Istiqlal Delitua Academic Year 2022/2023. The design of this research was descriptive quantitative research and the instrument used in this research was an objective test or multiple choices. The population of this research was 210 students. Then, the researchers used a simple random sampling technique to take the sample and chose 30 students. The researchers found out: first, the mean score of students’ ability in using conditional sentences was 77.86; it was categorized as a “good” level; second, the dominant type of students’ ability in using conditional sentences was “type I” with a mean score of 0.88 or 38%. It means the process of teaching and learning English, more specifically, in Conditional Sentences, at SMAS Istiqlal Delitua Academic Year 2022/2023 has reached the standard.